Observing HTI’s Da’wah Movement Following Perppu Number 2 of 2017 Concerning Community Organizations - Fatmawati Fatmawati; Kalsum Minangsih; Siti Mahmudah Noorhayati (UIN Sunan Kalijaga Yogyakarta, 2019)
This research was based on an academic concern regarding the dissolution of Hizbut Tahrir Indonesia (HTI) on July 19, 2017 through Perppu (Enactment of Government Regulation in Lieu of Law) Number 2 of 2017 concerning Community Organizations. This Perppu has changed the map of the HTI’s da'wah and political movements which were previously massive and dominant in various media and became silent at once. Previously known as the 411, the 212, and the 505 Muslim Movements which were led HTI people, then after the HTI dissolution, this organization seemed to be in suspended animation and vanished without a trace. Even HTI’s preaching movements on various online media under the organization’s guidance have been difficult to find. Based on this concern, the formulation of the problem in this study is as follows: first, what is the doctrine and anatomy of the HTI movement? Second, how was the HTI da’wah movement since the New Order until the issuance of Perrpu Number 2 of 2017? Third, what strategies are used by Hizbut Tahrir after the enactment of Perppu Number 2 of 2017? Fourth, what Counter Narrative reveals the HTI’s inconsistencies after the enactment of Perppu Number 2 of 2017 concerning Community Organizations? These questions will be answered qualitatively through descriptive explanation of the object being studied as behavior and an event with the main location in Indonesia with its information from actors and documents scattered in the electronic and print media, so that the data source is mostly literature and does not rule out the possible date from informants. In conclusion, the HTI movement as a da'wah and political organization will continue to exist despite being banned institutionally. Based on observation and discussion with several community leaders, HTI is continues recruiting new members, especially on public campuses which have become its hub, even though it is done with silent operations. In addition, national political contestation ahead of the 2019 presidential election is also very vulnerable to being ridden by HTI, either by continuing to spread propaganda or raise the issues of government failure in alleviating poverty, securing domestic assets, and the rule of law.